A new genus and species of philometrid (Nematoda) from the subcutaneous tissue of the crevalle jack, Caranx hippos (Osteichthyes), from the southern Gulf of Mexico - Moravec, Frantisek; Montoya-Mendoza, Jesús; Salgado-Maldonado, Guillermo (The Journal of parasitology, 2008)
A new genus and species of nematode, Caranginema americanum n. gen., n. sp. (Philometridae), are described from gravid, subgravid, and nongravid female specimens collected from the subcutaneous tissue of the fish (crevalle jack) Caranx hippos (Carangidae, Perciformes) from the coral reef El Cabezo, southern Gulf of Mexico, Mexico. Caranginema, assigned to the Philometrinae, differs from other genera of this subfamily mainly in the presence of 2 conspicuous parallel cordons on either side, extending along nearly the entire body length and demarcating narrow smooth lateral fields and in having the remaining body surface with numerous ornamentations forming irregularly scattered, transversely elongated narrow cuticular molds. The new species is characterized mainly by the presence of 3 large, sclerotized esophageal teeth protruded out of the mouth, the number and arrangement of cephalic papillae (8 papillae in 4 pairs of external circle and 4 single papillae of internal circle), the length and structure of the esophagus, and by the body length of gravid and subgravid females (267 and 258 mm, respectively). Caranginema americanum is the seventh philometrid species reported from marine and brackish water fishes in Mexico.
Keywords: Perciformes; Female; Dracunculoidea; nemoci ryb; infekce hlísticemi řádu Spirurida; Animals; Mexiko; Microscopy, Electron, Scanning; ženské pohlaví; zvířata; Spirurida Infections; mikroskopie elektronová rastrovací; Fish Diseases; Mexico